The Effect of Applying Scaffolding Method on Students' Programming Abilities at Surakarta State Vocational School - Steven Budi Sanjaya; Yusfia Hafid Aristyagama; Dwi Maryono (IJIE (Indonesian Journal of Informatics Education), 2025)
This research aims to determine the effect of applying the scaffolding method on the programming abilities of students at Surakarta Vocational School as measured by tests or programming ability tests. By using the scaffolding method, it is hoped that students' programming abilities will be better than conventional learning methods. The research used a quasi-experimental design with a pre-test and post-test control group design. In the research, the control class was not given treatment in learning activities, while the experimental class was given treatment in the form of a scaffolding method in learning activities. The research subjects were 72 class X students at a Vocational School in Surakarta obtained by cluster random sampling. Research data was obtained using pre-test and post-test which were prepared based on basic programming concepts using the Java programming language. Research data analysis was carried out using descriptive analysis techniques using the SPSS application. The results of the research show that the application of the scaffolding method has a good effect on the programming abilities of students at Surakarta Vocational School. This can be seen from the average programming ability test result for the experimental class which is higher than the control class (79.58 > 74.72). Additionally, the gain score analysis revealed that the improvement in the experimental class (49.72%) was significantly higher than the control class (41.94%). It can be concluded that the programming ability of the experimental class using the scaffolding method is better than the control class.